Corticotropin releasing factor-1 receptor antagonism associated with favorable outcomes of male reproductive health biochemical parameters - Khattab, Ahmed; Charlton, R. Will (Frontiers in Endocrinology, 2023)
Background: Disruption in androgen profiles and testicular adrenal rest tumors in males with congenital adrenal hyperplasia (CAH) can negatively affect sexual activity and fertility. Adrenal hyperandrogenism suppresses gonadotropin secretion and testicular adrenal rest tumors (TARTS), despite being noncancerous lesions, cause obstructive azoospermia and impaired testosterone (T) production. Circulating T in men with uncontrolled CAH is often predominantly adrenal in origin, which is reflected in high androstenedione/testosterone ratios (A4/T). Therefore, decreased luteinizing hormone (LH) levels and an increased (A4/T) are markers of impaired fertility in these individuals. Methods: Oral tildacerfont 200 to 1000 mg once daily (QD) (n=10) or 100 to 200 mg twice daily (n=9 and 7) for 2 weeks (Study 201), and 400 mg QD (n=11) for 12 weeks (Study 202). Outcomes measured changes from baseline in (A4), (T), (A4/T), and LH. Results: Mean T levels increased in Study 201 from 375.5 ng/dL to 390.5 ng/dL at week 2 (n=9), 485.4 ng/dL at week 4 (n=4) and 420.7 ng/dL at week 6 (n=4). In Study 202 T levels fluctuated in the normal range from 448.4 ng/dL at baseline to 412.0 ng/dL at week 12. Mean LH levels increased in Study 201 from 0.68 IU/L to 1.59 IU/L at week 2 (n=10), 1.62 IU/L at week 4 (n=5) and 0.85 IU/L at week 6 (n=4). In Study 202, mean LH levels increased from 0.44 IU/L at baseline to 0.87 IU/L at week 12. Mean A4/T decreased across both studies. In Study 201, the mean A4/T changed from a baseline of 1.28 to 0.59 at week 2 (n=9), 0.87 at week 4 (n=4), and 1.03 at week 6 (n=4). In Study 202, the (A4/T) decreased from baseline of 2.44 to 0.68 at week 12. Four men were hypogonadal at baseline; all experienced improved a (A4/T) and 3/4 (75%) reached levels <1. Conclusions: Tildacerfont treatment demonstrated clinically meaningful reductions in A4 levels, and (A4/T) with concomitant increased LH levels indicating increased testicular T production. The data suggests improvement in hypothalamic-pituitary-gonadal axis function, but more data is required to confirm favorable male reproductive health outcomes.